2020
DOI: 10.5713/ajas.20.0350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water scarcity during thermal-humidity exposure on the mineral footprint of sheep

Abstract: Objective: Combination of two stressors on alteration of mineral footprints in animals needs due attention to meet maximum production and welfare, particularly in grazing sheep. This study tested whether ewes (Ovis aries) exposed to water deprivation and thermal–humidity stressors had altered mineral footprints in their wool, serum, urine, and feces.Methods: Nine ewes (age = 3 years; mean body weight = 41±3.5 kg) were divided among a control group with free access to water, and treatment groups with water depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…This could be due to the fact that Ca and Mn are primarily stored in bones and are more likely to be mobilized from bones to muscles when a Zn deficiency disrupts mineral balance in the body. Nejad et al found that high levels of Ca in feed can inhibit Zn uptake ( 35 ), suggesting a possible competitive inhibitory relationship between Ca and Zn. The increase in Ca content in LD after the LZn treatment support this idea.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the fact that Ca and Mn are primarily stored in bones and are more likely to be mobilized from bones to muscles when a Zn deficiency disrupts mineral balance in the body. Nejad et al found that high levels of Ca in feed can inhibit Zn uptake ( 35 ), suggesting a possible competitive inhibitory relationship between Ca and Zn. The increase in Ca content in LD after the LZn treatment support this idea.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, the importance of trace elements in livestock and poultry production has been well documented [1]. Trace elements are among the natural needs of broilers and other domestic animals, and are added to their diets through mineral supplements [2,3]. Copper, selenium, iron, iodine, manganese, and zinc are the six elements in broiler diets that are given in the form of inorganic compounds (mainly oxides and sulfates).…”
Section: Introductionmentioning
confidence: 99%
“…The most important property of CTM is their high absorption and stability coefficient [5]. In fact, chelates of organic matter (especially proteins) and metal elements are effectively absorbed in the intestine and provide the opportunity not only to reduce the standard content of these minerals in the diet without adverse effects on the production characteristics of livestock and poultry, but also to reduce the environmental pollution caused by their cumulative aggregation [2,3]. Thus, there is an increasing interest in using organic forms of minerals compared to inorganic forms in animal nutrition.…”
Section: Introductionmentioning
confidence: 99%